2003
DOI: 10.1103/physrevd.68.047701
|View full text |Cite
|
Sign up to set email alerts
|

Universal threshold enhancement

Abstract: By assuming certain analytic properties of the propagator, it is shown that universal features of the spectral function including threshold enhancement arise if a pole describing a particle at high temperature approaches in the complex energy plane the threshold position of its two-body decay with the variation of T. The case is considered, when one can disregard any other decay processes. The quality of the proposed description is demonstrated by comparing it with the detailed large N solution of the linear s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
44
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 17 publications
(56 citation statements)
references
References 10 publications
12
44
0
Order By: Relevance
“…Nevertheless, threshold enhancement is indeed observed in nuclear matter experiments, both in πA → ππA ′ [23,24] and in γA → ππA ′ [25] reactions. Although the size of the effect is still under debate, a clear signal is seen in the scalar channel for increasing nuclear density as compared with the vector channel and this is in fair agreement with most theoretical analyses at finite nuclear density [26,27,28,29,30,31]. In contrast, finite temperature analyses show that this state remains broad even near the chiral phase transition despite the proximity of the pole to the two-pion threshold [12,30,32], which in practice does not produce any sizable enhancement in the scattering amplitude or cross section.…”
Section: Introductionsupporting
confidence: 84%
See 1 more Smart Citation
“…Nevertheless, threshold enhancement is indeed observed in nuclear matter experiments, both in πA → ππA ′ [23,24] and in γA → ππA ′ [25] reactions. Although the size of the effect is still under debate, a clear signal is seen in the scalar channel for increasing nuclear density as compared with the vector channel and this is in fair agreement with most theoretical analyses at finite nuclear density [26,27,28,29,30,31]. In contrast, finite temperature analyses show that this state remains broad even near the chiral phase transition despite the proximity of the pole to the two-pion threshold [12,30,32], which in practice does not produce any sizable enhancement in the scattering amplitude or cross section.…”
Section: Introductionsupporting
confidence: 84%
“…Although the size of the effect is still under debate, a clear signal is seen in the scalar channel for increasing nuclear density as compared with the vector channel and this is in fair agreement with most theoretical analyses at finite nuclear density [26,27,28,29,30,31]. In contrast, finite temperature analyses show that this state remains broad even near the chiral phase transition despite the proximity of the pole to the two-pion threshold [12,30,32], which in practice does not produce any sizable enhancement in the scattering amplitude or cross section. A striking possibility to be explored is that by increasing further the medium strength, the σ could become a ππ bound state, as suggested earlier in [33] and confirmed recently in [12,30,32].…”
Section: Introductionsupporting
confidence: 84%
“…The authors in [2,6] showed that the width grows with temperature, while the mass decreases slightly. This paper is organized as follows.…”
Section: Introductionmentioning
confidence: 99%
“…The line of analysis presented here has been applied also to the model with explicit O(4)-breaking external field [ 11,16], with parameters chosen the closest possible to the measured characteristics of the σ − π meson system. The behaviour found in this analysis proved generic also for the system with finite baryonic charge density.…”
Section: Resultsmentioning
confidence: 99%